Exposure to organophosphate insecticides, inappropriate personal protective equipment use, and cognitive performance among pesticide applicators - Chittrakul, Jiraporn; Sapbamrer, Ratana; Hongsibsong, Surat (Frontiers in Public Health, 2022)
Inappropriate use of personal protective equipment (PPE) among pesticide applicators may increase urinary organophosphate (OP) metabolite levels and subsequently increase risks of cognitive performance. Therefore, this study aims to (1) compare urinary OP metabolite levels and cognitive performance between pre-and post-pesticide application seasons; (2) PPE use and factors associated with PPE use linked to increased urinary OP metabolite levels during pesticide application; and (3) the association between urinary OP metabolite levels and cognitive performance. This longitudinal follow-up study on 79 pesticide applicators was carried out between October 2021 and January 2022. The applicators were interviewed, collected urine samples, and tested for cognitive performance in pre-and post-pesticide application seasons. The results found that the levels of urinary OP metabolites in post-application season were significantly higher than those in pre-application season (p <0.001). Multiple linear regression analysis found that increased total diethylphosphate (DEP) and total dialkylphosphate (DAP) levels were associated with not wearing gloves while mixing pesticides (beta (B)+standard error (SE) = -43.74+18.52, 95% confidence interval (95%CI) = -80.84, -6.64 for total DEP and -50.84+19.26, 95%CI = -89.41,-12.26 for total DAP) and also with not wearing a mask while spraying pesticides (+SE = -31.76+12.24, 95%CI = -56.28,-7.24 for total DEP and -33.20+12.63, 95%CI = -58.49,-7.92 for total DAP) after adjusting for covariates. The scores of Montreal Cognitive Assessment-Thai, Thai Mental State Examination, and Mini-Cognitive test in post-pesticide application were significantly lower than those in pre-pesticide application (p <0.001). However, no association was found between urinary OP metabolite levels and cognitive decline. Our findings indicate that inappropriate PPE use during pesticide application was the major factor affecting urinary OP metabolite levels among pesticide applicators. Wearing gloves when mixing pesticides and a mask when spraying pesticides were key factors in reducing occupational exposure to OP. Exposure to OP at low levels and for short periods of exposure may not affect cognitive performance significantly. Therefore, long-term exposure and exposure to high levels of OP should be investigated further.